Correlation between Platelet to Lymphocyte Ratio with C-Reactive Protein in COVID-19 Patients - Novianti Anggie Lestari; Dwi Retnoningrum (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Coronavirus 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Inflammation occurs when the body is infected with the virus. Platelets play a role in immune response and immunomodulation by activating P-Selectin Glycoprotein (PSGL) to the site of inflammation. Lymphocytes play a role through CD4 T-cells, B-cells producing specific viral antibodies, and CD8 cytotoxic T-cells by directly killing the virus in infected cells. This study aimed to prove the correlation between PLR and CRP as inflammation markers in COVID-19 patients. This study was a retrospective observational study with the cross-sectional approach at Dr. Kariadi Hospital, Semarang, for the period March-August 2020. Spearman test performed for analyzing data with p<0.05 was significant. Thirty-three confirmed COVID-19 patients with median value of PLR 218 (103-1609) and CRP 15.94 (1.24-200) mg/L were tested for correlation with a value of p=0.013 and r=0.427. The increase of PLR and CRP in COVID-19 patients was caused by an inflammatory process mediated by the immune response. High values in the blood were associated with disease severity and poor prognosis. There was a statistically significant moderate positive correlation between PLR and CRP in COVID-19 patients.